Masculinity and Precarity: Male Migrant Taxi Drivers in South China. (June 2018) - Choi, Susanne YP
This article examines how male rural-to-urban migrant taxi drivers' experience of a loss of control over their working conditions and increasing financial insecurity are driven by state regulation and market reorganization of the taxi industry, and their status as second class citizens in urban China. Precarity, as explored in this article, speaks to feelings of disempowerment, a profound sense of livelihood insecurity and a crisis of social reproduction that has resulted from workplace reorganization that marginalizes workers. The findings contribute to the study of precarity and masculinity by first unpacking how masculine identities are built around men's access to masculine service niches and their control over working conditions in these niches. It then shows how precariousness negates these male workers' sense of self by simultaneously taking away the control that distinguishes their work from factory employment and female-dominated service jobs; and undermining their capacity to meet the provider norm.